Vibration of Steel Joist-Concrete Slab Floors - Lenzen, Kenneth H. (Engineering Journal, 1966)
Developments in materials and technology have led to lighter types of construction in floors with little decrease in factors of safety. These economical methods of construction have resulted in occasional floors with insufficient stiffness to prevent noticeable vibration induced by human impact. This problem has not been limited to any type of construction or construction material. The Steel Joist Institute, in order to acquire basic knowledge and test data in the field of floor vibration, initiated and sponsored a research program at The University of Kansas. Copies of the final report can be obtained from either The University of Kansas or from the Steel Joist Institute at Washington, D. C. The program consisted of analytical and experimental work both in the field and laboratory. Two floors were built in the laboratory for control purposes, and to obtain floors which were subject to annoying vibrations. These floors were at the limit of the acceptable design range. Figure 1 shows the first floor loaded with dead weight to design load. In addition, measurements were taken on 46 different floors in the Kansas City area. The floors were designed for many different usages; offices, churches, schoolrooms, halls, and assembly rooms. The floors were in buildings in use for years as well as buildings under construction. The condition of the supported concrete slabs was a large variable. Some floors had badly cracked concrete, and others were in excellent condition. The thickness of the concrete varied as much as 2 in. from that indicated on the drawing. In only three floors of those investigated, would the disagreement between the predicted and measured frequency have been of any consequence if a vibration problem were present.